2012
DOI: 10.1186/1471-2431-12-148
|View full text |Cite
|
Sign up to set email alerts
|

Circulating hematopoietic stem cell count is a valuable predictor of prematurity complications in preterm newborns

Abstract: BackgroundThe frequency of preterm labour has risen over the last few years. Hence, there is growing interest in the identification of markers that may facilitate prediction and prevention of premature birth complications. Here, we studied the association of the number of circulating stem cell populations with the incidence of complications typical of prematurity.MethodsThe study groups consisted of 90 preterm (23–36 weeks of gestational age) and 52 full-term (37–41 weeks) infants. Non-hematopoietic stem cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1
21

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(46 citation statements)
references
References 53 publications
0
24
1
21
Order By: Relevance
“…11 Recently, we reported that the increased number of hematopoietic SCs (CD45 + lin-CD184 + ) circulating in CB is strongly associated with a lower risk of developing premature birth complications, including intraventricular hemorrhage, respiratory distress syndrome, infections, and anemia. 12 Furthermore, we observed that con centrations of a more immature, nonhematopoietic SC of the CD45-lin-CD184 + phenotype in CB are inversely associated with birth weight in preterm infants, suggesting that these cells might be involved in the maturation of the fetus. 12 We also observed that the relative number of circulating endothelial progenitor cells in CB was inversely associated with Apgar scores of preterm infants.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…11 Recently, we reported that the increased number of hematopoietic SCs (CD45 + lin-CD184 + ) circulating in CB is strongly associated with a lower risk of developing premature birth complications, including intraventricular hemorrhage, respiratory distress syndrome, infections, and anemia. 12 Furthermore, we observed that con centrations of a more immature, nonhematopoietic SC of the CD45-lin-CD184 + phenotype in CB are inversely associated with birth weight in preterm infants, suggesting that these cells might be involved in the maturation of the fetus. 12 We also observed that the relative number of circulating endothelial progenitor cells in CB was inversely associated with Apgar scores of preterm infants.…”
Section: Introductionmentioning
confidence: 72%
“…12 Furthermore, we observed that con centrations of a more immature, nonhematopoietic SC of the CD45-lin-CD184 + phenotype in CB are inversely associated with birth weight in preterm infants, suggesting that these cells might be involved in the maturation of the fetus. 12 We also observed that the relative number of circulating endothelial progenitor cells in CB was inversely associated with Apgar scores of preterm infants. A positive association between the number of endothelial progenitor cells with "early" phenotype (CD133 + /CD34 + /CD144 + ) and the risk of respiratory distress syndrome, retinopathy of prematurity, bronchopulmonary dysplasia, and infections was found; however, multivariate analyses revealed that an increase in endothelial progenitor cells was not an independent predictor of prematurity complications but was directly related to lower gestational age.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…It will be further highlighted information on novel therapeutic approach proposed by our group to build a basis for a potential discussion of the future clinical trials. turity (ROP), respiratory distress syndrome (RDS), bronchopulmonary dysplasia (BPD), necritizing enterocolitis (NEC), infections, and anemia, among others [5]. The etiology of these complications is multifactorial and includes a local and general hypoxic state, organ ischemia, and a broad-spectrum lack of adaptation to the extrauterine environment [5].…”
Section: Introductionmentioning
confidence: 99%